R-phase transformation in NiTi alloys. (November 2014) - Wang, X. B.; Verlinden, B.; Van Humbeeck, J.
<x content-type="archive" xml:space="preserve">Abstract</x> In near equiatomic NiTi alloys, the thermoelastic transformation between austenite and the R-phase shows unique properties, which make the R-phase transformation very promising for applications. In the present paper, the fundamental issues related to the R-phase transformation, especially the effects of different thermomechanical treatments, are reviewed. Inspired by the literature review, recent work on controlling the R-phase transformation temperature by low temperature aging treatments is summarised.